DOI’ MENRE DALAM PERKAWINAN MASYARAKAT DESA BERINGIN JAYA KECAMATAN BAEBUNTA SELATAN KABUPATEN LUWU UTARA DALAM PERSPEKTIF HUKUM ISLAM - Yulia Safitri, Eka; Firmansyah (MADDIKA : Journal of Islamic Family Law, 2024)
In the Bugis community's marriage customs, doi’ menre refers to a sum of money given by the groom's family to the bride's family to cover the wedding expenses. The aims of this research are to understand the concept of doi’ menre in Bugis marriages in Beringin Jaya Village, South Baebunta Subdistrict, North Luwu Regency, and to ascertain its perspective within Islamic law. This research employs a qualitative method. The findings indicate that the giving of doi’ menre in Bugis marriages in Beringin Jaya Village, South Baebunta Subdistrict, North Luwu Regency, constitutes a customary requirement that must be fulfilled before the marriage takes place. Its purpose is to honor the woman being married. The process of determining the amount of doi’ menre involves mutual deliberation between both families of the prospective bride and groom and is also determined according to the financial capacity of the groom's side. From an Islamic legal perspective, the giving of doi’ menre is permissible as it does not contradict Islamic law